MMSE multiuser detection for uplink DS-CDMA with regenerative cooperative relaying - Liu, Yan. (2010)
To meet contemporary and future demand for high speed and good quantity in communication transmission, advanced algorithms and techniques has been greatly studied and employed. In wireless mobile communication various forms of diversity has primary importance. Cooperative diversity transmission investigated in this paper is a kind of spatial diversity.